2017
DOI: 10.3847/1538-4357/aa80e3
|View full text |Cite
|
Sign up to set email alerts
|

RADYN Simulations of Non-thermal and Thermal Models of Ellerman Bombs

Abstract: Ellerman bombs (EBs) are brightenings in the Hα line wings that are believed to be caused by magnetic reconnection in the lower atmosphere. To study the response and evolution of the chromospheric line profiles, we perform radiative hydrodynamic simulations of EBs using both non-thermal and thermal models. Overall, these models can generate line profiles that are similar to observations. However, in non-thermal models we find dimming in the Hα line wings and continuum when the heating begins, while for the the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…2. For cases FQa and FQb, we see a dimming in both the line and the nearby continuum during the first 2 s. The dimming effect caused by non-thermal electrons seems a common phenomenon in flares and Ellerman bombs, which has already been reported in some previous simulations (Abbett & Hawley 1999;Allred et al 2006;Hong et al 2017). Dimming in this line is also seen in the calculation results of Sharykin et al (2017).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…2. For cases FQa and FQb, we see a dimming in both the line and the nearby continuum during the first 2 s. The dimming effect caused by non-thermal electrons seems a common phenomenon in flares and Ellerman bombs, which has already been reported in some previous simulations (Abbett & Hawley 1999;Allred et al 2006;Hong et al 2017). Dimming in this line is also seen in the calculation results of Sharykin et al (2017).…”
Section: Introductionsupporting
confidence: 86%
“…We assume an atmosphere in a 10 Mm quarter-circular loop structure. Following Hong et al (2017), we employ two different atmospheric models to construct the initial atmosphere. One is a quiet-Sun atmosphere, the same as in Hong et al (2017), which is based on the VAL3C model (Vernazza et al 1981); the other is a penumbral atmosphere that is based on the semi-empirical model of Ding & Fang (1989).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Reid et al (2017) and Hong et al (2017) used the radiative hydrodynamics code RADYN to model Ellerman bombs and found that temperature enhancements of up to ∆T =3000 K yielded Hα and Ca ii 8542 Å profiles similar to observations. Both studies also considered Mg ii k, where a larger energy deposition was required to obtain profile shapes similar to the observations, however, simultaneous agreement between all three diagnostics could not be achieved in either of those studies.…”
Section: Temperature Stratificationmentioning
confidence: 79%
“…The discovery of IBs led Fang et al (2017), and Hong et al (2017a) to investigate whether the EB models could be modified to produce Si IV emission. Fang et al (2017) considered temperatures of the hot component up to 15 kK, but then the chromospheric signatures were not consistent with the EB observations.…”
Section: Uv Burst Modelingmentioning
confidence: 99%